Genome-Wide Association Studies Detect Multiple QTLs for Productivity in Mesoamerican Diversity Panel of Common Bean Under Drought Stress - Valdisser, Paula Arielle Mendes Ribeiro; Müller, Bárbara S. F.; de Almeida Filho, Janeo Eustáquio; Morais Júnior, Odilon Peixoto; Guimarães, Cléber Morais; Borba, Tereza C. O.; de Souza, Isabela Pavanelli; Zucchi, Maria Imaculada; Neves, Leandro G.; Coelho, Alexandre S. G.; Brondani, Claudio; Vianello, Rosana Pereira (Frontiers in Plant Science, 2020)
Drought stress is an important abiotic factor limiting common bean yield, with great impact on the production worldwide. Understanding the genetic basis regulating beans’ yield and seed weight is a fundamental pre-requisite for the development of superior cultivars. The main objectives of this work were to conduct genome-wide marker discovery by genotyping a Mesoamerican panel of common bean germplasm, containing cultivated and landrace germplasms of broad origin, followed by the identification of genomic regions associated with productivity under two water regimes using different GWAS approaches. A total of 11,870 markers were successfully genotyped for the 339 genotypes, of which 3,213 were SilicoDArT and 8,657 SNPs derived from DArT and Capture-Seq, with MAF ≥ 0.05 and missing data <5%. The estimated LD extension, corrected for structure and relatedness (r2sv), was 98.63 kb and 124.18 kb for landraces and breeding lines, respectively. Germplasm was structured into landraces and lines/cultivars. We carried out GWAS for 100-seed weight (SW) and yield in field environments with and without water stress for three consecutive years, using single-, segment- and gene-based models. Higher number of associations at high-stringency was identified for the SW trait under irrigation, totaling ~185 QTLs for both single- and segment-based, while gene-based GWAS showed ~220 genomic regions containing ~650 genes. For SW under drought, 18 QTLs were identified for single- and segment-based and 35 genes by gene-based GWAS. For yield, under irrigation, 25 associations were identified, while under drought the total was ten using both approaches. In addition to the consistent associations detected across experiments, these GWAS approaches provided important complementary QTL information (~221 QTLs; 650 genes; r2 from 0.01% to 32%). Several QTLs were mined within or near candidate genes playing significant role in productivity, providing better understanding of the genetic mechanisms underlying these traits and making available new molecular tools to be used in marker-assisted breeding. The findings also allowed the identification of genetic material (germplasm) with better yield performance under drought, promising to a common bean breeding program. Finally, the high diverse Mesoamerican panel available for the analysis of any relevant traits in common bean is of great scientific value.